Neuroprotective effects of fermented soybean products (Cheonggukjang) manufactured by mixed culture of Bacillus subtilis MC31 and Lactobacillus sakei 383 on trimethyltin-induced cognitive defects mice. (2nd July 2016) - Go, Jun; Kim, Ji Eun; Kwak, Moon Hwa; Koh, Eun Kyoung; Song, Sung Hwa; Sung, Ji Eun; Kim, Dong Sup; Hong, Jin Tae; Hwang, Dae Youn
Abstract : Objectives : This study aimed to investigate the beneficial effects of Cheonggukjang (CGK) manufactured by mixed culture of Bacillus subtilis MC31 and Lactobacillus sakei 383 on neurotoxic damages. Methods : The specific aspects of brain functions were measured in Institute for Cancer Research (ICR) mice that had been pretreated for 4 weeks with three difference doses of CGK before trimethyltin (TMT) treatment. Results : The short- and long-term memory loss induced by TMT treatment was significantly improved in the CGK-pretreated group in a dose-dependent manner. The number of dead cells in the granule cell layer of the dentate gyrus was decreased in the TMT/CGK-cotreated group relative to the TMT/vehicle-treated group, whereas significant suppression of acetylcholinesterase (AChE) activity was observed in the same group. Additionally, a dose-dependent increase in nerve growth factor (NGF) concentration, activation of the NGF receptor signaling pathway including the TrkA high affinity receptor and p75 NTR low affinity receptor, and decline in Bax/Bcl-2 level was measured in all TMT/CGK-treated groups, although a decrease in the active form of caspase-3 was observed in the TMT/H-CGK-treated group. Furthermore, superoxide dismutase (SOD) activity was enhanced in the TMT/CGK-treated group, whereas the level of malondialdehyde (MDA), a marker of lipid peroxidation, was 43–58% lower in the TMT/CGK-treated group than the TMT/vehicle-treated group. Discussion : These results demonstrate that CGK fermented by mixed culture of B. subtilis and L. sakei could exert a wide range of beneficial activities for neurodegenerative diseases, including Alzheimer, Parkinson, and Huntington disease.